Spatial-Temporal Occurrence of Sea Urchins and their Grazing along Diani-Chale Lagoonal Reefs, Mombasa - Sergon, Nancy; Chemoiwa, Emily J.; Mulei, Josephine (African Journal of Education,Science and Technology (AJEST), 2022)
Seagrass plays a key role in coastal ecosystems influencing environmental abiotic parameters and supporting a great abundance and diversity of species belonging to many phyla. Overgrazing by herbivores has been postulated as a potential threat to seagrass in Kenya. Indirectly, fishing may result in sea urchin outbreaks caused by removal of sea urchin predators. Therefore the purpose of this study was to determine the spatial and temporal occurrence of sea urchins and grazing on seagrass along Diani lagoonal reefs, in Kwale. Three sites, namely, Mvuleni, Chale, and Mwaepe, were selected and quadrats randomly used in sampling sea urchins and seagrass. Moreover, healthy and degraded sections were identified in each of the selected sites and 40 samples were obtained from each study site and for each season using one-meter square quadrats (N = 360). Descriptive statistics and inferential statistics were applied in determining abundance, density, and diversity of sea urchins and their seasonal and temporal influence on seagrass cover. Research findings indicated that the abundance and diversity of sea urchins and seagrass varied according to seasons. The density of sea urchins was highest during the northeast monsoon and more degraded habitats when compared to healthy ones. Regression outcome demonstrated that the density of sea urchins was statistically significant negative predictor (r = -0.699) of the proportion of seagrass cover and accounted for 48.8% of variation. Therefore, the study concludes that sea urchins are major macro-grazers that contribute to overgrazing and degradation of the seabed. This study recommends further studies to identify specific biotic and abiotic factors that affect their distributions, employ longitudinal design to demonstrate trends of sea urchin migration, overgrazing, and degradation of seabed along the Kenyan coastline.